Transcriptional regulators involved in responses to volatile organic compounds in plants. - Nagashima, A.; Higaki, T.; Koeduka, T.; Ishigami, K.; Hosokawa, S.; Watanabe, H.; Matsui, K.; Matsui, K.; Touhara, K.
Field studies have shown that plants growing next to herbivore-infested plants acquire higher resistance to herbivore damage. This increased resistance is partly due to regulation of plant gene expression by volatile organic compounds (VOCs)released by plants that sense environmental challenges such as herbivores. The molecular basis for VOC sensing in plants, however, is poorly understood. Here, we report the identification of TOPLESS-like proteins (TPLs)that have VOC-binding activity and are involved in VOC sensing in tobacco. While screening for volatiles that induce stress-responsive gene expression in tobacco BY-2 cells and tobacco plants, we found that some sesquiterpenes induce the expression of stress-responsive genes. These results provided evidence that plants sense these VOCs and motivated us to analyze the mechanisms underlying volatile sensing using tobacco as a model system. Using a pulldown assay with caryophyllene derivative-linked beads, we identified TPLs as transcriptional co-repressors that bind volatile caryophyllene analogs. Overexpression of TPLs in cultured BY-2 cells or tobacco leaves reduced caryophyllene-induced gene expression, indicating that TPLs are involved in the responses to caryophyllene analogs in tobacco. We propose that unlike animals, which use membrane receptors for sensing odorants, a transcriptional co-repressor plays a role in sensing and mediating VOC signals in plant cells.
Keywords: RECEPTOR; PLANT BIOCHEMISTRY; LIGAND-BINDING PROTEIN; TRANSCRIPTION REGULATION; TRANSCRIPTION COREPRESSOR; ODORANT; CHEMICAL SENSING; PLANT VOLATILE PERCEPTION; VOLATILE ORGANIC COMPOUNDS (VOCS); DEFENSE INDUCTION; TRANSCRIPTIONAL CO-REPRESSOR PROTEIN; TRANSCRIPTION FACTOR; GENE REGULATION; OLFACTION